2014
DOI: 10.1080/00223980.2014.913000
|View full text |Cite
|
Sign up to set email alerts
|

Bi-Directional Relationship Between Self-Regulation and Improved Eating: Temporal Associations With Exercise, Reduced Fatigue, and Weight Loss

Abstract: Severely obese men and women (body mass index ≥ 35 ≤ 55 kg/m(2); M(age) = 44.8 years, SD = 9.3) were randomly assigned to a 6-month physical activity support treatment paired with either nutrition education (n = 83) or cognitive-behavioral nutrition (n = 82) methods for weight loss. Both groups had significant improvements in physical activity, fatigue, self-regulation for eating, and fruit and vegetable intake. Compared to those in the nutrition education group, participants in the behavioral group demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 41 publications
1
12
0
3
Order By: Relevance
“…One study 27,29 included mostly men (83%), three studies 2224 included women only, and the rest 25,26,28,3035 included 58–88% women. Seven studies 2225,30,31,34,35 did not report racial/ethnic distribution and one study 26 only reported the percentage of black participants (37%).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One study 27,29 included mostly men (83%), three studies 2224 included women only, and the rest 25,26,28,3035 included 58–88% women. Seven studies 2225,30,31,34,35 did not report racial/ethnic distribution and one study 26 only reported the percentage of black participants (37%).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies included primarily white participants (97–100%), 32,33 and two other studies reported samples of non-Hispanic white (34–53%) and black participants (44–62%). 27,28 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations